Pembuatan Semir Sepatu dari Kulit Pisang Cavendish dengan Abu Merang Sebagai Pewarna Alami - Sakya Qonita Qurrotu'ain; Nisriina Qothrunnada; Fatichah Lutfi Zata Aqmar; Susanti Rahayu (Jurnal Integrasi Sains dan Quran, 2024)
Shoe polish is a consumer product used to buff, waterproof and improve the appearance of shoes, thereby extending the durability of footwear. Shoe polish is actually not good for health. Moreover, shoe polish contains the harmful ingredient nitrobenzene which has a very bad effect on health. In Indonesia, cavendish bananas are widely cultivated commercially. However, banana peel waste unconsciously accumulates along with the consumption of cavendish bananas. The solution of merang ash is very good as a natural black colorant because it contains carbon. The purpose of this study was to determine how the process of making shoe polish from cavendish banana waste with the addition of merang ash. This type of research is descriptive quantitative research and the focus of the research is the manufacture of shoe polish with cavendish banana peel as the basic ingredient and merang ash as a natural colorant. The collection methods used include observation, literature study, and documentation. The tests carried out include physical tests and organoleptical tests. Based on the tests that have been carried out, this research produces shoe polish with a solid texture, non-sticky, non-irritating, has a dry time of 1 minute and has good performance in resistance to water splashes.